Identification of Antibody and Small Molecule Antagonists of Ferroportin-Hepcidin Interaction - Ross, Sandra L.; Biswas, Kaustav; Rottman, James; Allen, Jennifer R.; Long, Jason; Miranda, Les P.; Winters, Aaron; Arvedson, Tara L. (Frontiers in Pharmacology, 2017)
The iron exporter ferroportin and its ligand, the hormone hepcidin, control fluxes of stored and recycled iron for use in a variety of essential biochemical processes. Inflammatory disorders and malignancies are often associated with high hepcidin levels, leading to ferroportin down-regulation, iron sequestration in tissue macrophages and subsequent anemia. The objective of this research was to develop reagents to characterize the expression of ferroportin, the interaction between ferroportin and hepcidin, as well as to identify novel ferroportin antagonists capable of maintaining iron export in the presence of hepcidin. Development of investigative tools that enabled cell-based screening assays is described in detail, including specific and sensitive monoclonal antibodies that detect endogenously-expressed human and mouse ferroportin and fluorescently-labeled chemically-synthesized human hepcidin. Large and small molecule antagonists inhibiting hepcidin-mediated ferroportin internalization were identified, and unique insights into the requirements for interaction between these two key iron homeostasis molecules are provided.